A Zirconium Oxide Nanoparticle Modified Screen‐printed Electrode for Anodic Stripping Determination of Daclatasvir Dihydrochloride. Issue 5 (6th February 2019) - Hendawy, Hassan A. M.; Eldin, Ghada M. G.; Fekry, Amany M.
Abstract: A novel, sensitive and rapid voltammetric method applied for daclatasvir dihydrochloride (DSV.2HCl) detection in raw material, human plasma and urine using square wave voltammetry at a nano‐screen printed electrode (SPE) based on synthesized zirconium oxide nanoparticles (ZrO2 NPs). The attention to zirconium oxide nanoparticle syntheses arises from its likely use in making an electrode material in the electroanalytical process. Anodic stripping square wave voltammetric peaks have been recorded at the optimum conditions of drug solution as pH, scan rate, accumulation time and accumulation potential. Morphology of the used nanoparticles has been performed by scanning electron microscope (SEM) and transmission microscope (TEM). ZrO2 NPs were applied to screen printed electrode (ZrO2 ‐MSPE) giving a new sensor to detect the DSV.2HCl drug. ZrO2 NPs were tested for their electroactivity in improving electrodes sensitivity. The modified electrode has been used for the analysis of DSV.2HCl in spiked serum, spiked urine and pharmaceutical formulation. Abstract :